Switchgrass Germplasm Resources. Issue 6 (1st November 2015) - Casler, Michael D.; Vogel, Kenneth P.; Harrison, Melanie
ABSTRACT: Switchgrass ( Panicum virgatum L.) is an important native grass and dominant member of the tallgrass prairie ecosystem. It is used for conservation, restoration, livestock feed production, and bioenergy feedstock production. The purpose of this review is to describe the biological and geographical basis for switchgrass germplasm diversity and to provide a resource for scientists and outreach personnel to find switchgrass germplasm to meet their needs. Upland and lowland ecotypes represent the most important polymorphism in switchgrass, with distinct but overlapping geographic distributions. Variation in ploidy exists within both ecotypes, with 2 n = 4 x = 36 the dominant ploidy in the lowland ecotype and 2 n = 8 x = 72 the dominant ploidy in the upland ecotype. Ploidy is a strong barrier to gene flow, but ecotype is a weak barrier, with up to 10% of random individuals demonstrating some evidence for upland‐lowland hybridization in their ancestry. Latitudinal and, to a lesser extent, longitudinal differentiation exists within each ecotype, such that most wild populations and cultivars are not well adapted more than one hardiness zone from their place of origin. Plant breeding can alter this relationship by creating populations with improved cold tolerance, for example, increasing the adaptation range of an individual cultivar. The USDA National Plant Germplasm System maintains the national switchgrass collection, which is available for research and breeding purposes.